Aplikasi Media Pembelajaran Menanam Sayuran Hidroponik Berbasis Android - Jerrycho Azarea Aditama; Jati Sasongko Wibowo (STEKOM PRESS, 2023)
Learning Media applications that use an Android-based material delivery system are expected to facilitate the delivery of material, where previously material was only found in books and the internet. Learning materials that only come from books reduce the reader's understanding because there are only text and pictures. This is what underlies the selection of the thesis title